The decreasing albedo of the Zhadang glacier on western Nyainqentanglha and the role of light-absorbing impurities - B. Qu; J. Ming; S.-C. Kang; G.-S. Zhang; Y.-W. Li; C.-D. Li; S.-Y. Zhao; Z.-M. Ji; J.-J. Cao (Atmospheric Chemistry and Physics, 2014)
A large change in albedo has a significant effect on glacier ablation. Atmospheric aerosols – e.g. black carbon (BC) and dust – can reduce the albedo of glaciers and thus contribute to their melting. In this study, two main themes were explored: (1) the decrease in albedo of the Zhadang glacier on Mt. Nyainqentanglha between 2001 and 2012, as observed by the Moderate Resolution Imaging Spectroradiometer (MODIS) on-board the Terra satellite, and the correlation of this albedo with mass balance; and (2) the concentrations of BC and dust in the glacier measured during 2012, and the associated impacts of these impurities on albedo and radiative forcings (RF). The average albedo of the Zhadang glacier from the MODIS increased with the altitude and fluctuated but had a decreasing trend (−0.003 a−1) during the period 2001–2012, with the highest (0.722) in 2003 and the lowest (0.597) in 2009 and 2010. The mass balance of the glacier has a positively significant correlation with its surface albedo derived from MODIS. Snow samples were collected on the Zhadang glacier to measure the BC and dust in the summer of 2012. The impacts of BC and dust on albedo reduction in different melting conditions were identified with the SNow ICe Aerosol Radiative (SNICAR) model initiated by in situ observation data. The sensitivity analysis showed that BC was a major factor in albedo reduction when the glacier was covered by newly fallen snow. Nevertheless, the contribution of dust to albedo reduction can reach as high as 56%, much exceeding that of BC (28%), when the glacier experiences strong surficial melting and its surface is almost bare ice. The average RF caused by dust could increase from 1.1 to 8.6 W m−2, exceeding the RF caused by BC after snow was deposited and surface melting occurred in the Zhadang glacier. This implies that it may be dust that primarily dominates the melting of some glaciers in the inner Tibetan Plateau during melting seasons, rather than BC.